Effects of maternal advanced lipoxidation end products diet on the glycolipid metabolism and gut microbiota in offspring mice - Pang, Wenwen; Zhang, Bowei; Zhang, Junshi; Chen, Tianyi; Han, Qiurong; Yang, Zhen (Frontiers in Nutrition, 2024)
Introduction Dietary advanced lipoxidation end products (ALEs), which are abundant in heat-processed foods, could induce lipid metabolism disorders. However, limited studies have examined the relationship between maternal ALEs diet and offspring health. Methods To investigate the transgenerational effects of ALEs, a cross-generation mouse model was developed. The C57BL/6J mice were fed with dietary ALEs during preconception, pregnancy and lactation. Then, the changes of glycolipid metabolism and gut microbiota of the offspring mice were analyzed. Results Maternal ALEs diet not only affected the metabolic homeostasis of dams, but also induced hepatic glycolipid accumulation, abnormal liver function, and disturbance of metabolism parameters in offspring. Furthermore, maternal ALEs diet significantly upregulated the expression of TLR4, TRIF and TNF-α proteins through the AMPK/mTOR/PPARα signaling pathway, leading to dysfunctional glycolipid metabolism in offspring. In addition, 16S rRNA analysis showed that maternal ALEs diet was capable of altered microbiota composition of offspring, and increased the Firmicutes/Bacteroidetes ratio. Discussion This study has for the first time demonstrated the transgenerational effects of maternal ALEs diet on the glycolipid metabolism and gut microbiota in offspring mice, and may help to better understand the adverse effects of dietary ALEs.